Interactive Media to Increase Family Support and Medication Adherence in Hypertension Patients - Masnah, Cek; Suharti , Suharti; Daryono, Daryono (Journal of Health Education, 2024)
Background: Failure to comply with antihypertensive medication risks more serious complications. Researchers examined interactive media to increase compliance with hypertension sufferers effectively. Methods: The research was carried out with a case-control design. The research sample was taken using non-probability sampling, namely 50 people in the intervention group and 50 in the control group. Before the intervention was carried out, all respondents underwent initial measurements. The final measurement was carried out approximately 1.5 months after the intervention. Bivariate analysis used the Mann-Whitney test and Wilcoxon Signed Rank Test. To analyze the effectiveness of interactive media using the N-Gain Score test. Results: After the intervention, there were significant differences between the intervention and control groups regarding knowledge (p=0.000), family support (p=0.000), and compliance with hypertension sufferers (p=0.000). There was an increase in compliance in both the intervention and control groups, but the increase in the intervention group was higher. Based on the N-Gain Score test, in the intervention group, there was an increase in knowledge of 75.04%, family support of 64.36%, and compliance of 75.63%. Meanwhile, in the control group, the increase in knowledge was 34.60%, family support 32.84%, and compliance 19.38%. Conclusions: Interactive media effectively increases hypertension sufferers' knowledge, family support, and compliance.